Comparison of pain during endovenous laser ablation of the great saphenous vein with ultrasound-guided femoral nerve block with local anesthesia (Annals of Medical Research, 2023)
Aim: The endoluminal laser ablation technique is used to treat greater saphenous vein insufficiency. Endovenous laser ablation may be associated with significant pain when performed under standard local tumescent anesthesia. The purpose of this study was to investigate the efficacy of femoral nerve blocks for analgesia during endovenous ablation in patients with lower extremity venous insufficiency.Materials and Methods: Sixty-seven patients of ASA physical status I and II, with ages ranging between 29 and 55 years, and who underwent endovenous laser ablation due to greater saphenous vein insufficiency were retrospectively analyzed. All patients received tumescent anesthesia (TA). However, one group received a femoral nerve block (FNB) under ultrasound-guidance before the procedure. The FNB (n=34) was performed at the level of the inguinal ligament, by injecting 20 ml of 0.5% bupivacaine solution under ultrasound-guidance. After the blocks, endovenous laser ablations and other treatments were performed in the standard manner. After the procedures, a visual analogue pain scale (VAS) values of patients were collected from records for pain assessment. The VAS, volume of TA solution, mean heart rate, mean arterial pressures, nause-vomiting and additional consumption of analgesics were recorded at postoperative 0,1,2,4 and 6h, respectively.Results: Postoperative mean heart rate, arterial pressure and nause-vomiting did not differ between the groups (p>0.05). While the perioperative VAS values ​​were
Keywords: Laser ablation; Femoral block; Tumescent anesthesia